2017
DOI: 10.1038/bjc.2017.164
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-199b-5p attenuates TGF-β1-induced epithelial–mesenchymal transition in hepatocellular carcinoma

Abstract: Background:Accumulating evidence indicates that N-cadherin is a cell adhesion molecule that has critical roles in tumour progression. However, the role of N-cadherin in hepatocellular carcinoma (HCC) remains controversial.Methods:This study aims to investigate the expression status of N-cadherin and its molecular mechanisms in HCC.Results:The expression of N-cadherin was markedly overexpressed in HCC tissues and cell lines. We identified that miR-199b-5p binds to the 3′-UTR of N-cadherin mRNA, thus decreasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 39 publications
2
33
1
1
Order By: Relevance
“…Mengtao Ma et al found that MAGI2 promotes TGF‐β1‐induced EMT and migration and invasion of breast cancer cells under the direct action of miR‐487a . miR‐199b‐5p promotes cell aggregation, suppresses cell invasion and migration and inhibits TGF‐β‐induced EMT in hepatocellular carcinoma by inhibiting N‐cadherin . In several studies, miR‐130a‐3p was shown to decrease in cancer tissues and inhibit cell invasion, migration, and EMT .…”
Section: Discussionmentioning
confidence: 99%
“…Mengtao Ma et al found that MAGI2 promotes TGF‐β1‐induced EMT and migration and invasion of breast cancer cells under the direct action of miR‐487a . miR‐199b‐5p promotes cell aggregation, suppresses cell invasion and migration and inhibits TGF‐β‐induced EMT in hepatocellular carcinoma by inhibiting N‐cadherin . In several studies, miR‐130a‐3p was shown to decrease in cancer tissues and inhibit cell invasion, migration, and EMT .…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1 can increase miR-155 and promote EMT, invasion and metastasis of HCC in vitro (Li, Wang, et al, 2017). miR-199b-5p can attenuate EMT in HCC by targeting TGF-β1 signal (Zhou et al, 2017). miR-663 overexpression can regulate HCC cell apoptosis through targeting TGF-β1 (Huang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the miR-199b expression level is decreased in hepatocellular carcinoma. Hepatocellular carcinoma patients with low miR-199b levels show shorter overall survival and progression-free survival rates than those patients with high miR-199b levels (24,25). In bladder cancer, miR-199b expression is downregulated, which is associated with poor prognosis (26).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, miR-199b is found to play tumour suppressive roles in multiple human cancer types. For example, miR-199b overexpression suppresses cell proliferation and epithelial-mesenchymal transition, and increases radiosensitivity in hepatocellular carcinoma (24,25). Fang et al found that miR-199b overexpression restrains cell growth, colony formation and metastasis (27,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation